MODERN LEGAL DOCTRINE OF CIVILIANS PROTECTION IN THE ARMED CONFLICTS - Tarnopolova, M. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
The article examines the protection of civilians in armed conflict and its main components, through the perspective of modern legal doctrine. The urgency of the formation of legal doctrine is related to the development of European integration processes taking place in Ukraine, in order to bring the national legal system closer to international humanitarian law and human rights law in efforts to stop and prevent the escalation and resumption of armed conflicts, enhancement counter-terrorism and prevention of violent extremism. The importance of legal doctrine in the lawmaking process and the necessity to develop domestic legal doctrine of protection of civilians in armed conflicts as a source of convincing nature for bodies of legislative and executive power, as to form a legal system of protection of civilians in armed conflicts, taking into account "state’s elements of responsibility for protection ". It was stated that the concept of "Responsibility for protection" is a political and legal obligation based on the principles of international law and international human rights treaties, and the framework documents on the protection of civilians, which has already been adopted by a number of States, are based on best practices and define clear institutional powers and responsibilities for the protection of civilians and civilian objects during the conduction of military actions, and will intensify their efforts to implement human rights priorities in the future. The division of protection of civilians in armed conflict is divided into four concepts depending on the subjects (actors) involved in the protection of non-combatants and giving their characteristics.